Description of the Level of Knowledge and Awareness of Pregnant Women about Gingivitis at the Ngroto Community Health Center, Cepu District, Blora Regency - Hartanti, Hartanti; Indira Salsabila, Shafa (Jurnal Kesehatan Gigi, 2024)
Increased hormones during pregnancy such as estrogen and progesterone during pregnancy can cause gingivitis. Pregnant women who experience gingivitis are at risk of giving birth to LBW babies and premature births. Factors that can affect gingivitis in pregnant women are the knowledge and awareness of pregnant women about gingivitis.This study aims to describe the level of knowledge and awareness of pregnant women about gingivitis at the Ngroto Health Center, Cepu District, Blora Regency. This type of research is descriptive observational using a cross sectional design. The research sample is pregnant women who carry out pregnancy checks at the Ngroto Health Center. The research sample was taken using total sampling and obtained 42 respondents. The level of knowledge and awareness of pregnant women about gingivitis was measured using a questionnaire. Using ordinal scale data. The descriptive analysis used is the frequency distribution. The results showed that 8 pregnant women (19.0%) had a good level of knowledge and 15 pregnant women (35.7%) had a good level of awareness. Most of the pregnant women in Ngroto Health Center have a low level of knowledge and awareness about gingivitis